Optimal economic dispatch by fast distributed gradient - Chaojie Li; Xinghuo Yu; Wenwu Yu (2014 13th International Conference on Control Automation Robotics & Vision (ICARCV), 2014)
Concerning on optimal economic dispatch, interior point method via 6-logarithmic barrier is employed to reformulate the cost function of power generation. Fully distributed technology-enabled algorithm is developed to solve the economic dispatch. More specifically, the minimum connected dominating set based distributed algorithm aims at efficiently allocating the task of supply-demand balance for the whole power grid. A fast gradient based distributed optimization method is designed to fast converge to optimal solution. The simulations illustrate the effectiveness and good performance of our algorithms.